Measuring the Height of Volcanic Clouds Using Weather Radar : Case Study Mount Sinabung Eruptions in Medan, Indonesia - Heningtiyas, Hesti; Achmadi, Budhi; Supriyadi, Asep Adang; Arief, Syachrul; Charolydya, Rindita (Indonesian Journal of Geography, 2025)
Apart from being used to observe hydrometeorological phenomena, weather radar can also be used to observe volcanic eruptions. Weather radar reflectivity data can describe the estimated height of volcanic eruptions, while the HYSPLIT (Hybrid Single-Particle Lagrangian Integrated Trajectory) model describes the trajectory or direction of distribution of eruption clouds. BMKG's single polarization C-Band weather radar at the Regional Office I in Medan was able to observe several eruptions of Mount Sinabung. Mount Sinabung is about 50 km from the Medan Weather Radar hence is still within radar coverage. Several eruptive activities of Mount Sinabung can be observed from the Medan Weather Radar, using Maximum (MAX) and VCUT (Vertical Cut) products to obtain information on the height of volcanic eruptions and eruption characteristics. While, the HYSPLIT model developed by ARL-NOAA is used to determine the direction of distribution of volcanic ash immediately after the eruption. The MAX and VCUT weather radar products and the results of NOAA HYSPLIT model for several events in this study show that the eruption height in weather radar observations is higher than the HYSPLIT model and the direction of volcanic ash distribution is different from Volcanic Observatory Notice for Aviation (VONA) observations.Received: 2024-05-24 Revised: 2025-06-26 Accepted: 2025-08-15Published: 2025-08-19